Multicultural Education at SDN 36 Cakranegara (Post-Conflict Study of Two Villages in Mataram City) - Wadi, Hairil; Junaidi, Eka (Universitas Tanjungpura, 2024)
This research is descriptive qualitative research which is motivated by the emergence of various conflicts that occur in society. The aim of the research is to find out how multicultural education and multicultural values are implemented at SDN 36 Cakarnegara after the conflict between two villages in Mataram City. This research uses a descriptive qualitative approach by collecting data through interviews, observation and documentation. Meanwhile, data analysis is done by reducing data, presenting data and providing conclusions. The research results show that: post-conflict multicultural education in 36 Cakranegara is carried out through: visits, creating an atmosphere of harmony, modeling, introducing other people's cultures; invite students to imtak activities that apply multicultural values after the conflict at SDN 36 Cakranegara, namely: Values of harmony, cooperation, concord, appreciation, respect, compassion, tolerance, love of the homeland.